Design and investigation of charge plasma-based TMD heterojunction TFET biosensor for ultrasensitive detection - Monika Kumari; Niraj Kumar Singh; Vinay Kantipudi; Manodipan Sahoo (Scientific Reports)
Abstract In this work, a charge plasma TMD heterojunction tunnel FET-based dielectrically modulated biosensor is designed and investigated for biosensing applications. In the proposed biosensor, WTe2 and MoS2 serve as the source and channel material, respectively to form the heterojunction. Whereas the channel-drain junction is a homojunction formed by MoS2. The advantage of heterojunction has been exploited to overcome the low I ON and ambipolar behavior of TFET, which results in the enhancement of sensitivity. The charge plasma doping has been utilized to mitigate random dopant variations, reduce manufacturing expenses, and simplify the fabrication process. Non-equilibrium green’s function (NEGF)-based simulator and SILVACO TCAD, a 2-D device simulator have been utilized to simulate the electrical characteristics of the proposed biosensor. Uniform filling of the cavities in biosensors is not always practically possible; thus, the issue of partial hybridization is also considered in this work. The proposed biosensor (for k = 9) achieves a high sensitivity of 1010, an I ON /I OFF ratio of 1014, and a low subthreshold swing of 39 mV/decade. Finally, the proposed biosensor is benchmarked with contemporary works of the literature and it has been observed that the presented charge plasma TMD heterojunction TFET (CP-TMD-HJ-TFET)-based biosensor has emerged to have a superior sensitivity (i.e. I ON /I OFF ratio) which is ∼ 4 decades higher than the maximum sensitivity reported by any contemporary biosensor.